Human Rights Concern in International Investment Law: A Study of Indian International Investment Agreements - Chhachhar, Varun; Negi, Monika; Singh, Prashant; Kumar, Niharika (UI Scholars Hub, 2025)
The interaction of human rights and investment protection obligations in international investment law is on the rise. Human rights have been cited in claims and defenses of the parties and in the reasoning of the tribunals. Since majority of international investment agreements lack clarity and do not express the use of the term ‘human rights’, experts question the legitimacy of such usage. Given the alleged backlash and ongoing reforms in international investment law, the lack of human rights concern in international investment law needs proper investigation. This paper investigates the issue in the Indian context. After the adoption of its new Model Bilateral Investment Treaty in 2015, India has unilaterally terminated most of its international investment agreements and is negotiating new ones. This paper identifies the ways in which the issue of human rights is invoked in international investment law, with an analysis of the investment treaty practice of India using a doctrinal method. Indian international investment treaty practices before the 2015 Model BIT mostly did not include the term human rights, but the BITs signed post 2015 Model do expressly use the term human rights, albeit in the form of voluntary obligations. Additionally, India made human-rights based arguments and the tribunals did mention human rights in awards to which India was a party but the tribunals stressed upon the need to have express human rights provision in the treaty, which it mostly lacked.